IDENTIFIKASI PENDIDIKAN MULTIKULTURAL DALAM FESTIVAL SENI BUDAYA PADA KOMUNITAS SASAK-ISLAM DAN BALI-HINDU DI BAYAN, KABUPATEN LOMBOK UTARA - I Wayan Ardhi Wirawan (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
This study aims to identify the implementation of multicultural education in culturalfestivals carried out by the Sasak-Islam and Bali-Hindu communities in the Bayan region, NorthLombok Regency. This phenomenon is related to the existence of cultural competencies, especiallyin cultural arts attractions that are actualized by both ethnic religious communities. The culturaldiversity in the location is recognized and accepted as part of a shared life in realizing socialharmony. In this regard, the community in that location has a cultural awareness to accept thedifferences that exist as a frame to create excitement and add to the beauty of the togethernessframe. These conditions in terms of multicultural education aspects indicate the existence ofspace to build awareness to dilute existing barriers to differences so as to realize mutualisticsocial relations as inculturation of multicultural educational values ??in the midst of a pluralityof cultures that exist in social space. Identification of the implementation of multicultural educationvalues ??operating behind the acceptance and recognition of existing differences is to buildawareness to improve the quality of life, both individually and in groups. Awareness of therecognition and acceptance of existing cultural differences as part of reality is related to theestablishment of recognition of multiple truths and at the same time delaying metanarations thatposition a single truth. The values ??of multicultural education are in line with postmodernismthinking that provides space for multiculturalism theorists in building awareness to recognizethe plurality of cultures in realizing harmony in the frame of diversity in knit diversity.